Hasil belajar Fiqih siswa selama transisi kurikulum: Studi longitudinal - Khusnul Ma'arif; Asrori Asrori; Ika Puspitasari (Curricula: Journal of Curriculum Development, 2026)
Curriculum transition represents a dynamic aspect of educational policy that can influence classroom practices and students’ learning outcomes. This study examines changes in students’ fiqh learning outcomes during the transition from the Kurikulum 2013 (K13) to the Kurikulum Merdeka at MI Muhammadiyah 28 Sumberagung. A quantitative longitudinal before-after design was employed, involving the same cohort of students. Data were obtained from Fiqh report grades in the even semester of Grade 3 under the K13 (2024/2025) and the even semester of Grade 4 under the Kurikulum Merdeka (2025/2026). Descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon signed-rank test were applied for analysis. The results show an increase in the mean Fiqh score, with a statistically significant difference and a large effect size. These findings indicate that the Kurikulum Merdeka, supported by teaching modules, may be associated with improved Fiqh learning outcomes, while acknowledging the influence of assessment practices and contextual factors.